Reseña de Casas Gómez, Miguel (dir.) & Rodríguez-Piñero Alcalá (ed.) (2008). X Jornadas de Lingüística - Gerard Fernández Smith (Pragmalingüística)
Se trata de Reseña de Casas Gómez, Miguel (dir.) & Rodríguez-Piñero Alcalá (ed.) (2008). X Jornadas de Lingüística.